X Users’ perspectives toward the use of alternate universe as an online platform to improve EFL writing skill - Bunga, Rara Jingga; Warni, Silih (CAHAYA PENDIDIKAN, 2023)
The purpose of this study to investigates the perspective of fanfiction readers on Twitter to improve their daily writing skills through Alternate Universe. This study used a qualitative descriptive method to obtain data from interviews. The type of method is a phenomenological approach by exploring the participant's subjective perspective on the Alternate Universe phenomenon on Twitter. The researcher interviewed five sources of Twitter users based on criteria have been settled, such as age, how often they read, how they felt about reading Alternate Universe, and their opinion about the Alternate Universe phenomenon. Data analysis applied consists of reduction of data, display of data, and conclusion illustrating or verification. The researcher used a variety of data-gathering procedures, such as in-depth interviews, to collect data or obtain information in a more detailed manner. The results of research through in-depth interview process with various informants' backgrounds. Based on interviews, they get heartfelt every time they read AU. Also, Alternate Universe can provide them with new knowledge. Thus, they could learn something new, such as new vocabulary, and discover motivation to write neatly.